3D‐Printed Radiopaque Bioresorbable Stents to Improve Device Visualization (Adv. Healthcare Mater. 23/2022). Issue 23 (8th December 2022) - Ding, Yonghui; Fu, Rao; Collins, Caralyn Paige; Yoda, Sarah‐Fatime; Sun, Cheng; Ameer, Guillermo A.
Abstract : Bioresorbable Stents In article 2201955, Cheng Sun, Guillermo A. Ameer, and co‐workers report a method to confer X‐ray contrast to 3D printed polymeric bioresorbable stents (BRS) through the incorporation of the clinically used contrast agent iodixanol into a citrate‐based polymer ink. The 3D‐printed BRS has strong X‐ray visibility, mechanical competence, and excellent in vitro biocompatibility, characteristics that are important for successful clinical use.